Il "rex sacrorum" in Africa: testimonianze - Gabrielli, Chantal (Studia Historica. Historia Antigua, 2010)
RESUMEN: Questo articolo analizza alcune epigrafi provenienti da due province romane dell'Africa (Mauretania Caesariensis e Numidia), che presentano la carica di rex sacrorum. Tale sacerdozio, creato a Roma nei primi secoli délia repubblica è presente nel contesto africano in época imperiale con una valenza precisa: il termine rex sacrorum sembra essere la traduzione in latino di una carica religiosa púnica e indicherebbe forse un'autorità religiosa locale. ABSTRACT: This paper analyses some inscriptions from two Roman provinces of Africa (Mauretania Caesariensis and Numidia), which have the title rex sacrorum. This priesthood, created at the start of the Republic, appears in the African context in the imperial age with a further value; the rex sacrorum seems to be the translation in Latin of a Neo-Punic word, that is a native priesthood, perhaps a chief religious authority.